Utilizing foam-structured hydroxypropyl methylcellulose oleogels with curcumin for deep-fried chicken nuggets in carnauba wax-canola oil oleogel - Niaz Mahmud; Joinul Islam; Reza Tahergorabi (Journal of Agriculture and Food Research)
In this study, foam-structured hydroxypropyl methylcellulose was used to structure cod liver oil into oleogel. Different concentrations of curcumin (0, 1.1, 2.2, 3.3, and 4.4 mg/100g of chicken nuggets) were added to the oleogels and incorporated into the chicken nuggets. Subsequently, samples were deep-fried in an oleogel frying medium prepared with carnauba wax and canola oil (10g/100g). Our results revealed that the addition of 4.4 mg/100g of curcumin led to the highest fat uptake reduction and moisture retention compared to the control and 1.1 mg/100g of curcumin (P < 0.05). Additionally, the addition of 4.4 mg/100g of curcumin exhibited consistently higher oxidative stability, as indicated by thiobarbituric acid reactive substances (TBARS), during the 30-day storage period at −18 °C compared to the control (P < 0.05). Notably, treated samples did not show any alteration in ash and protein contents, color, texture, pH values, sensory attributes, or microscopic structures of the fried chicken products. Furthermore, fatty acid analysis revealed that the samples containing 4.4 mg/100g of curcumin had significantly lower levels of saturated fatty acids and higher levels of monounsaturated and polyunsaturated fatty acids than the control (P < 0.05). Overall, the study demonstrates that adding curcumin in a carrier setting to deep-fried chicken products can improve the products by reducing fat uptake and extending oxidative stability.